Perubahan Karakteristik Organoleptik Udang Vanamei (Litopenaeus Vannamei) Dengan Menggunakan Berbagai Perlakuan - Evi Liviawaty; Nitie Ismi; Ima Nur Halimah; Anjelly Maulina; Atik Nur Latifah (Jurnal Kajian dan Penelitian Umum, 2023)
Vanname shrimp (Litopenaeus vanname) is a type of seafood that has a fairly short shelf life and is susceptible to quality deterioration, therefore it is necessary to add or treat Vanname shrimp. This study aims to determine the effectiveness and which treatment is best for the shelf life of vanname shrimp. The proposed treatments are control, 20% lime, 20% salt solution, and 100g garlic, with storage for 7 days with temperatur 5 - 10℃. The parameters observed were changes in organoleptic characteristics of vanname shrimp (Litopenaeus vanname) during the 7-day shelf life. The statistical test used is the average test (Mean). The results showed that the best treatment was using lime with a concentration of 20% where the texture and appearance had the highest value to the panelists. But the aroma has a fairly good treatment of the aroma of vanname shrimp (Litopenaeus vanname) in a 7-day storage period.